Molecular survey of Toxoplasma gondii in cattle and buffaloes and phylogenetic position of Pakistani isolates based on ITS-1 gene - Taalay, Iram; Iqbal, Rana Khalid; Asif, Muhammad; Ahmad, Aqib; Amjad, Muhammad; Anwar, Farhana Naureen; Iqbal, Furhan (Elsevier Sci Ltd, 2022)
Toxoplasma gondii (T. gondii) is a facultative heterogeneous parasite that belongs to Apicomplexa and can infect almost all warm-blooded animals, including ruminants, birds and humans. To date, no information is available about the molecular investigation of T. gondii in large ruminants from Pakistan. In the present study, prevalence, risk factors and genetic diversity of this parasite were evaluated by using PCR based on ITS-1 gene followed by sequencing of three selected positive PCR products. A total of 310 blood samples from cattle (N = 190) and buffaloes (N = 120) were collected from randomly selected farms located in Rajanpur district in Punjab (Pakistan). The overall infection rates of T. gondii were 12.2% (23/190) and 0% (0/120), respectively, in cattle and buffaloes. All studied epidemiological factors were not found associated with T. gondii infection in cattle. Sequence analysis of our T. gondii isolates infecting cattle revealed only one sequence considered as the most represented genetic variant (GV1) among T. gondii isolates around the world. Phylogenetic analysis revealed that ITS-1 partial sequences of our isolates clustered with those from T. gondii isolates infecting goats and birds from Pakistan and other isolates found in several animal species from different worldwide countries like China, Thailand, Poland, Canada, USA and Brazil. Our report indicates a natural infection with T. gondii of cattle for the first time in Pakistan by using molecular method. This study is important to the design of control strategy against this parasite in order to improve the output of livestock sector which is the main income source of the population in Pakistan.
Keywords: Toxoplasma gondii; Cattle and buffaloes; Pakistan; Molecular detection; Phylogenetic analysis; ITS-1 gene